Effect of alley cropping of white popinac (Leucaena latisiliqua) on crop productivity and soil fertility under rainfed condition - PRASAD, ARJUN; SINGH, RATAN (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted during 1981-82 to 1990-91 on a clay soil to study the effect of alley cropping of white popinac [Leucaena latisiliqua L.] Gillis; syn L. leucocephala (L.) de Wit] with field crop of sorghum [Sorghum bicolor (L.) Moench), sorghum + pigeonpea (Cajanus cajan (L.) Millsp.] and pigeonpea + blackgram (Phaseolus mungo L.) on crop productivity and soil fertility under rainfed condition. Hedge rows of white popinae at 3.75 m spacing grown with field crops reduced the grain yield of sorghum, sorghum + pigeonpea and pigeonpea + blackgram by 12.4, 13.6 and 16.9% respectively compared with the expected reduction of 20%. But the reduction in green-fodder yield of white popinac was 65.4, 73.6 and 63.0% compared with the expected reduction of 80% sole cropping at 0.75m spacing. The values. of land-equivatent ratio of 1.20-1.22 under white popinae grown with field crops were higher than of sole cropping. White popinac with sorghum + pigeonpea intercropping gave overall higher yield advantage by producing higher biomass as grain and fodder. Field crops with white popinac also improved the soil-fertility status by increasing the organic carbon, and ,the available N and P content of soils.